For all ordered triples ( p , q , r ) , define the polynomial f p , q , r ( x ) = x 3 − p x 2 + q x − r . Let a 1 , a 2 , a 3 , b 1 , b 2 , b 3 , c 1 , c 2 , c 3 be (not necessary distinct) positive real numbers such that the roots of f a 1 , a 2 , a 3 ( x ) are b 1 , b 2 , b 3 and the roots of f b 1 , b 2 , b 3 ( x ) are c 1 , c 2 , c 3 . What is the maximum possible value of b 1 + 3 9 3 b 3 + a 1 + 1 4 + 3 b 1 + 2 b 2 + b 3 ?
This problem is posed by Zi Song Y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution, and a nice problem!
The first part of the solution looked like you knew the solution & accordingly framed the problem, & ah! Yes you did! :p
the problem is somewhat not nice, since the way you add and subtract must be done after you know the answer is 4
ZI SONG I LOVE YOU!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
wow nice long explanation god I wish I was as smart as people in this site, I just guessed it XD well not totally guessed it. I just got
b1 = c1+c2+c3
b2 = c1c2+c1c3+c2c3
b3 = c1c2c3
so I figured that since the denominator in the first half has b1 in it and the numerator has b3 in it, the result which maximizes the equation has to be the result which gets the biggest b3 while getting the smallest possible b1. if c1=c2=c3 it will get that result since b3/b1 will be (c^3)/3c which yields the biggest possible value. and then I just started doing c=2,c=3.c=4... and got 4 as the biggest result. "Cauchy-Schwarz Inequality"... I still have a long way to go I guess
Can you elaborate a little on how Cauchy-Schwarz was applied in the second-to-last line? You seem to have applied it to the numerators and just added the denominators.
Log in to reply
( b 1 a 1 2 + b 2 a 2 2 + . . . + b n a n 2 ) ( b 1 + b 2 + . . . + b n ) ≥ ( a 1 + a 2 + . . . + a n ) 2 , by the Cauchy-Schwarz inequality.
Log in to reply
Ah, I see now, thank you.
Im sorry but i still couldnt get the cauchy-schwarz inequality part. It's |x.y| <= ||x|| ||y||
Log in to reply
@Edmund Heng – If you write out the components of x as x 1 , x 2 , . . . , x n and y as y 1 , y 2 , . . . , y n , you can manipulate this into another common form of the inequality: ( Σ x i y i ) 2 ≤ ( Σ x i 2 ) ( Σ y i 2 ) .
Using x i = b i a i and y i = b i gives the inequality above.
Log in to reply
@Dan Rubery – Thanks!! i got it! Nice one, never thought of this usage before
By Vieta's relations, we get: b 1 = ∑ c i ; b 2 = ∑ c i c j ; b 3 = c 1 c 2 c 3 & a 1 = ∑ b i (that's all we need)
Observe that: a 1 + 1 = ( 1 + c 1 ) ( 1 + c 2 ) ( 1 + c 3 ) & that by A.M-G.M,
3 c 1 + c 2 + c 3 ≥ 3 c 1 c 2 c 3 ⇒ 3 + c 1 + c 2 + c 3 ≥ 3 + 3 3 c 1 c 2 c 3 with equality iff c 1 = c 2 = c 3
Let S : = b 1 + 3 9 3 b 3 + a 1 + 1 4 + 3 b 1 + 2 b 2 + b 3
Plugging in all values we get by rearrangement,
S = c 1 + c 2 + c 3 + 3 9 3 c 1 c 2 c 3 + ( 1 + c 1 ) ( 1 + c 2 ) ( 1 + c 3 ) 4 + 3 ∑ c i + 2 ∑ c i c j + c 1 c 2 c 3
≤ 1 + 3 c 1 c 2 c 3 3 3 c 1 c 2 c 3 + 1 + 1 + c 1 1 + 1 + c 2 1 + 1 + c 3 1
= 4 + 1 + c 1 1 + 1 + c 2 1 + 1 + c 3 1 − 1 + 3 c 1 c 2 c 3 3
For equality c 1 = c 2 = c 3 = c ,
S m a x = 4 + 1 + c 3 − 1 + c 3 = 4 .
Unfortunately, for you argument to work, you must have 1 + c 1 1 + 1 + c 2 1 + 1 + c 3 1 − 1 + 3 c 1 c 2 c 3 3 ≤ 0 for all c 1 , c 2 , c 3 (not necessarily equal).
And this is actually false, for example for c 1 = 8 , and c 2 = c 3 = 1 . What this really means is that you gave up too much room when you used the AM-GM inequality the way you did. This is a subtle inequality, with no known simple proof.
The AM-GM inequality was correct, but I think you're pointing out at the fact that after using the inequality, I'm adding variables to both sides, which were involved in the inequality. I thought that since I'm adding the same value(whatever that might be) to both sides,there won't be a problem,though not expecting such a disparity. However the inequality in that case, as you have pointed, will be still correct,except the equality part.
You say S < 4 + some positive quantity, but S = 4 + that quanitity, so basically you don't achieve an upper bound(with which S might be equal to). Please correct me if I'm missing something & also clarify how I 'gave up too much room'...
I think you mean ideally the sequence should approach it's maximum from negative side, but'<' doesn't really provide bounding value,& what is the problem if a sequence might approach it from positive side?
Log in to reply
As was explained, in your last line of
S ≤ 4 + 1 + c 1 1 + 1 + c 2 1 + 1 + c 3 1 − 1 + 3 c 1 c 2 c 3 3 ,
the RHS is not bounded above by 4 .
In fact ,if c 1 = 8 , c 2 = 1 , c 3 = 1 , we get the value of 4 + 9 1 . In this case, why must we still have S ≤ 4 , if all we can show is S ≤ 4 + 9 1 ?
By taking larger values, c 1 = n 3 , c 2 = c 3 , we get
4 + 1 + n 3 1 + 1 − 1 + n 3
which approaches 5 as n approaches infinity.
Hence, your initial AM-GM bound gave up too much room.
Log in to reply
And 1 more thing to all Brilliant staff: Please don't get annoyed if I comment anything trivially wrong on this forum(personally speaking), since most of this I learnt from Brilliant, & essentially this is a learning process. Thanks again Calvin L. & Alexander B.
Correct! Nice explanation of the inner part. I got it Challenge Master & Alexander B. Thanks for clarifications. Well, was this an influence which drove you to give an interesting inequality problem this week (Algebra Level 4)?? I hope yes. :)
Problem Loading...
Note Loading...
Set Loading...
Let x = c 1 , y = c 2 . z = c 3 , a = b 1 , b = b 2 , c = b 3 , d = a 1 . By Vieta's Formula, x + y + z = a , x y + y z + z x = b , x y z = c , a + b + c = d . Hence, x + 1 x + y + 1 y + z + 1 z = 3 − ( x + 1 1 + y + 1 1 + z + 1 1 ) = 3 − x y z + ( x y + y z + x z ) + ( x + y + z ) + 1 ( x y + y z + x z ) + 2 ( x + y + z ) + 3 = 3 − a + b + c + 1 2 a + b + 3 = 3 − d + 1 2 a + b + 3 . Thus, x + 1 x + y + 1 y + z + 1 z = 3 − d + 1 2 a + b + 3 = 4 − d + 1 4 + 3 a + 2 b + c .
Thus, by the Cauchy-Schwarz Inequality, we get
4 − d + 1 4 + 3 a + 2 b + c = x + 1 ( x ) 2 + y + 1 ( y ) 2 + z + 1 ( z ) 2 ≥ x + y + z + 3 ( x + y + z ) 2 ≥ a + 3 ( 3 3 x y z ) 2 = a + 3 9 3 c , where the last inequality holds by AM-GM.
Thus, a + 3 9 3 c + d + 1 4 + 3 a + 2 b + c = b 1 + 3 9 3 b 3 + a 1 + 1 4 + 3 b 1 + 2 b 2 + b 3 ≤ 4 . Equality holds when c 1 = c 2 = c 3 = 1 . (and possibly other values.) Thus, N = 4 .